Patent as Object of Fiduciary Guarantee in Banking Credit Practices - Bernadete Nurmawati; Dewi Iryani; Tarmudi Tarmudi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Intellectual property is interesting to study since it has a very important role in the advancement of the economy in this era of globalization. Intellectual Property Rights (IPR) are rights that arise from the results of the human brain's thinking that produce a product or process that is useful for the community. IPR includes intangible movable objects as regulated in article 499 of the Civil Code. This intangible object is the result of human thought and the object of ownership is a movable object that can be transferred to another party so that it can be used as a fiduciary guarantee as regulated in Law no. 13 of 2016 concerning Patents (Patent Law). Article 108 paragraph 1 states that "Patent rights can be used as objects of fiduciary guarantee". However, patent rights as objects of fiduciary guarantee in a bank's loan practice are currently unavailable due to obstacles in its implementation. There is no special Asset Appraisal Agency that assesses the economic value of patent rights so that it can be used as a credit guarantee. This makes it difficult for patents to be used as a fiduciary guarantee. To realize patents as objects of fiduciary guarantee, firm and detailed juridical support is needed regarding IPR assets as objects of bank credit guarantees. The valuation of patented assets must be supported by the Patent Regulations protected by the Bank Loan Guarantee and the need for legal access under the Bank Indonesia Regulations to support the patents that are protected by the Trustee Guarantee. So there should be an appraisal agency that can assess a patent right so that it can improve the people's economy and advance the national economy.